A new higher order shear deformation theory for static, vibration and buckling responses of laminated plates with the isogeometric analysis. (15th November 2018) - Shi, Peng; Dong, Chunying; Sun, Fuzhao; Liu, Wenfu; Hu, Qiankun
Abstract: A new hyperbolic tangent shear deformation theory (HTSDT) for the static, free vibration and buckling analysis of laminated composite plates is presented. In the present theory, shear stresses disappear at the top and bottom surfaces of the plates and shear correction factors are no longer required. Weak forms of the static, free vibration and buckling analysis for laminated composite plates based on the HTSDT are then derived and are numerically solved using the isogeometric analysis (IGA). The proposed formulation requires C 1 continuity generalized displacements, whereas the basis functions used in IGA can perfectly fulfill this requirement. Based on the available solutions in the literature, the present method shows high accuracy and efficiency when numerical examples are solved.